2008
DOI: 10.1038/modpathol.2008.99
|View full text |Cite
|
Sign up to set email alerts
|

Active matrix metalloproteinase-7 is associated with invasion in buccal squamous cell carcinoma

Abstract: Protein microarrays have shown that matrix metalloproteinase-7 is upregulated in head and neck squamous cell carcinomas, but its role in local tissue invasion is still uncertain. We investigated the expression of active matrix metalloproteinase-7, using tissue microarray, immunohistochemistry, and western blotting, in oral tissues from 24 patients with buccal squamous cell carcinoma, and correlated the findings with clinicopathological features. Normal buccal tissue samples from the same patients, obtained at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
(44 reference statements)
0
33
0
2
Order By: Relevance
“…The sites of OSCC occurrence in patients from the East are different from those in the West. 18 The predominant sites in Korea are gingivae and tongue, according to our statistics (Table 1). Moreover, clinicopathologic factors including histopathologic grade and TNM classification can provide some prognostic information in patients with OSCC, although detection of local deep invasion and potential metastases remains limited.…”
Section: Discussionmentioning
confidence: 98%
“…The sites of OSCC occurrence in patients from the East are different from those in the West. 18 The predominant sites in Korea are gingivae and tongue, according to our statistics (Table 1). Moreover, clinicopathologic factors including histopathologic grade and TNM classification can provide some prognostic information in patients with OSCC, although detection of local deep invasion and potential metastases remains limited.…”
Section: Discussionmentioning
confidence: 98%
“…Using immunohistochemistry and flow cytometry, they also detected high levels of expression of extracellular matrix metalloproteinase inducer in these cells. Another research group found that tumour tissues from 9 out of 24 cases of buccal SCC with mandibular invasion were stained strongly for active MMP-7, compared to 15 cases without invasion of the adjacent bone [25]. This is the first study demonstrating that MMP-7 is correlated with mandibular invasion, a significant observation which is consistent with the demonstration by others that secretion of MMP-7 by prostate and breast cancer cells is capable of cleaving the receptor activator of nuclear factor-κB ligand (RANKL) to an active soluble form, which then induces osteoclast formation and bone resorption [26,27].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 97%
“…Accumulated evidence showed a positive correlation between MMP7 expression and the invasive potential of cancers (18,19). Previous study demonstrated that knockdown or overexpression of MMP7 alters tumorigenicity.…”
mentioning
confidence: 99%
“…Like other MMPs, the activity of MMP7 is regulated at multiple levels, including gene expression, spatial localization, zymogen activation, and inhibition by its endogenous inhibitor (14,17). In contrast to other MMPs, which usually are expressed in stromal tissues, MMP7 is expressed mainly in tumor cells (18,19) and enhances tumor progression by inhibiting apoptosis in cancer cells, by reducing cell adhesion, or by inducing angiogenesis or both (20).…”
mentioning
confidence: 99%